PERKEMBANGAN KURIKULUM PENDIDIKAN DI INDONESIA DARI MASA KE MASA - Adeliya Putri Ananda; Hudaidah Hudaidah (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
Education is not limited by time and space. Education continues to develop as the times go by which aims to improve the quality of education itself. One of the important organs in education is the curriculum. The curriculum in education has a very big role in determining the progress of education in a country. Writing scientific articles aims to better understand the development of the curriculum in Indonesia from time to time which has undergone changes starting from the 1947 curriculum to the 2013 curriculum. The curriculum is always changing to meet the needs of society and adapt to the times. In writing scientific articles, the writer uses historical research methods. In the historical research method, the writer uses many reference sources in the form of relevant journals and books that support the writing of these scientific articles. The results of this discussion indicate that the curriculum in Indonesia has been developed 10 times, namely in 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006 and 2013 which are still in use today.